Quality of life of children with respiratory pathology against the background of connective tissue dysplasia - V. S. Ledneva; L. V. Ulianova; A. N. Gaponenko (Лечащий Врач, 2023)
Background. "Quality of life" includes 12 parameters reflecting socio-economic conditions and cultural and moral aspects of human life. The state of health is an integral component of the quality of life. Without health, social functioning becomes impossible. The study of the quality of life reflects a more complete picture of the disease, and also shows the effectiveness of therapeutic and restorative measures in patients. Of particular relevance is the assessment of the quality of life of patients with respiratory pathology, given its leading position among the child population for many years.Objective. The presence of connective tissue dysplasia in children with diseases of the lower respiratory tract, it contributes to the development of severe and complicated forms of the disease, as well as disability of patients. In this regard, the study of the quality of life of patients in this category is necessary.Materials and methods. During the study of the quality of life of 237 children with bronchopulmonary diseases in the age range from 2 to 18 years, a detailed examination was conducted, including a questionnaire, anamnesis collection, physical examination, laboratory (hemogram; determination of the level of type I collagen C-terminal telopeptide), functional (electrocardiography, computer flowmetry). In the presence of indications, patients underwent an X-ray examination of the chest organs, an examination by a neurologist, a medical geneticist, an orthopedist. The presence of DST was established when at least 6 clinical and instrumental markers of connective tissue disorders were detected in the patient, involvement of at least 2 body systems, an increase in the level of type I collagen C-terminal telopeptide.Conclusion. Connective tissue dysplasia negatively affects the quality of life of patients with bronchopulmonary pathology, reducing the level of psychosocial functioning of children with bronchial asthma and acute bronchitis and limiting physical functioning in patients with community-acquired pneumonia, which is due to a more severe course and prolonged persistence of symptoms of the disease.